2021
DOI: 10.1680/jstbu.19.00095
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane testing of masonry walls retrofitted with oriented strand board timber panels

Abstract: Several studies on different techniques can be found on retrofitting existing unreinforced masonry (URM) walls using varieties of materials ranging from reinforced plaster, grout and epoxy injection to fibre-reinforced polymers. Still, there is a significant lack of experimental data that consider using a material such as oriented strand board (OSB) timber panels, which can be easily sourced around the globe, and are considered to be economical and sustainable. Hence, this paper presents the first stage of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The integrated approach adopted in this study has been articulated in The full description of the second phase which precedes the study presented in this paper can be found in (46). The second phase showed that the application of OSB panel at the back of masonry prisms greatly influenced its out-of-plane behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrated approach adopted in this study has been articulated in The full description of the second phase which precedes the study presented in this paper can be found in (46). The second phase showed that the application of OSB panel at the back of masonry prisms greatly influenced its out-of-plane behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…The styrene-free vinylesterhybrid mortar is a high-performance injection mortar, which is approved for fixings in both perforated and solid brick. The adhesive anchor connection has been identified as the best-performed connection from the connection type studied in the small-scale test campaign described by (46). The criteria for selecting the connection type are guided by the requirements of European Technical Approval (61), which ensure that the selected anchorages are fit for use in solid masonry subjected to either static or quasi-static loading which was tested in this study.…”
Section: Test Specimens Constituentsmentioning
confidence: 99%
“…Three of these were tested as plain MP while the remaining six specimens were retrofitted with an 18 mm-thick OSB timber panel using two different types of connections: C1 (adhesive anchor-a threaded dry rod with an injectable chemical adhesive) and C2 (mechanical connection-a threaded dry rod with a plastic anchor). The purpose of this test [18] is to provide a simplified means of gathering data on the flexural strength of plain and timber-retrofitted MP. Precisely, the experiment evaluates the out-of-plane performance of OSB panel in retrofitting URM prisms by comparing the toughness, flexural strength, out-of-plane load capacity and displacement of both plain and OSB-retrofitted masonry prisms.…”
Section: Stage 2: Small-scale Test (Flexural Bond Strength Of Masonry Prism)mentioning
confidence: 99%
“…Although this paper focuses on the numerical study, still, sufficient information about the experimental studies are provided in this section, with special focus on the applied testing methodology and the primary findings. The reader is referred to previous works [15,18,19] for the details of experimental works on the material characterisation, small-scale and large-scale tests, respectively.…”
Section: Experimental Studymentioning
confidence: 99%
“…Such a decision is supported by experimental data at disposal [24]. The experimental tests analysed correspond to a flexural bond strength test on a 665 × 215 × 102.5 mm 3 masonry prism [36] and an out-of-plane loading test on a 1115 × 1115 × 215 mm 3 masonry wall [37]. A brief overview of the experimental works carried out at the George Earle Lab at the University of Leeds is provided in section 2.…”
Section: Introductionmentioning
confidence: 99%